Effects of exercise training on stress-induced vascular reactivity alterations: role of nitric oxide and prostanoids - Bruder-Nascimento, Thiago [UNESP]; Silva, Samuel T. [UNESP]; Boer, Patrícia A.; Cordellini, Sandra [UNESP] (Associação Brasileira de Pesquisa e Pós-Graduação em Fisioterapia, 2015)
Background: Physical exercise may modify biologic stress responses. Objective: To investigate the impact of exercise training on vascular alterations induced by acute stress, focusing on nitric oxide and cyclooxygenase pathways. Method: Wistar rats were separated into: sedentary, trained (60-min swimming, 5 days/week during 8 weeks, carrying a 5% body-weight load), stressed (2 h-immobilization), and trained/stressed. Response curves for noradrenaline, in the absence and presence of L-NAME or indomethacin, were obtained in intact and denuded aortas (n=7-10). Results: None of the procedures altered the denuded aorta reactivity. Intact aortas from stressed, trained, and trained/stressed rats showed similar reduction in noradrenaline maximal responses (sedentary 3.54±0.15, stressed 2.80±0.10*, trained 2.82±0.11*, trained/stressed 2.97± 0.21*, *P<0.05 relate to sedentary). Endothelium removal and L-NAME abolished this hyporeactivity in all experimental groups, except in trained/stressed rats that showed a partial aorta reactivity recovery in L-NAME presence (L-NAME: sedentary 5.23±0,26#, stressed 5.55±0.38#, trained 5.28±0.30#, trained/stressed 4.42±0.41, #P<0.05 related to trained/stressed). Indomethacin determined a decrease in sensitivity (EC50) in intact aortas of trained rats without abolishing the aortal hyporeactivity in trained, stressed, and trained/stressed rats. Conclusions: Exercise-induced vascular adaptive response involved an increase in endothelial vasodilator prostaglandins and nitric oxide. Stress-induced vascular adaptive response involved an increase in endothelial nitric oxide. Beside the involvement of the endothelial nitric oxide pathway, the vascular response of trained/stressed rats involved an additional mechanism yet to be elucidated. These findings advance on the understanding of the vascular processes after exercise and stress alone and in combination.
Keywords: Vasodilator prostanoids; Nitric oxide; Exercise training; Acute stress; Aorta reactivity; Physical therapy